SEJARAH PERBANKAN SYARIAH DI INDONESIA - Ikrar Agus Pepi A (Jurnal Program Pascasarjana Ilmu Hukum Universitas Islam As-Syafi'iyah, 2016)
Sharia banking is anything that concerns about the Bank of Shari'ah and Unit EffortsShari'ah, includes institutional, business activities as well as the manner and process ofcarrying out its business activities. Just as with conventional banks, Islamic banks also offercustomers the bank is in the conventional banking products. Only difference withconventional bank is in terms of pricing, both the sale price and the purchase price. Theproducts on offer is certainly doing your best to really Islami, including in providingservices to its customers. If the specific risks that would be causing varying degrees of bankprofits include liquidity risk, credit risk and interest rates, and risk capital. However,Islamic banks insyaa God trying not face the risk of interest, even though in an environmentwhere the prevailing dual banking system increased the interest rate on conventionalmarkets may have an impact on the increased risk of switching to conventional banks.